(untitled) (Eurasian Medical Research Periodical, 2025)
This article is dedicated to the pharmacognostic and biological structure of the lavender plant, its species, and its medicinal applications. The paper discusses the historical origins, distribution, morphological features, and main species of lavender, including Lavandula angustifolia (English lavender) and Lavandula intermedia (lavandin). The flowers and other parts of the plant are rich in essential oils, which are widely used in pharmacology, cosmetics, and the perfume industry. Lavender, especially its essential oils, with their calming, antibacterial, and anti-inflammatory properties, play an important role in the production of natural medicinal products. The article also provides information on recent research and industrial development in Uzbekistan regarding the cultivation of lavender and the production of natural therapeutic products